Competing against the biggest organisations in the world: How Sevilla FC Can Utilize Data and Digital Platforms to Compete Internationally - Sevilla FC case study - Lindström,Joel; Belcari,Giovanni (2026)
The sports industry is one of the most challenging and constantly evolving industries, yet simultaneously, the smaller and medium-sized clubs face a severe challenge of competing against the biggest and best-known brands in the world. The sports literature is limited to marketing and studying global mega-brands; this thesis addresses the gap in strategic management literature concerning both sports/football and scale neutralisation through digital growth internationally. The purpose was to understand how Sevilla FC, a medium-sized football club, can stay relevant and strategically reposition itself. The selected method was a single case study, utilizing semi-structured interviews with the club's digitalisation and internationalisation departments. The empirical findings demonstrate that to neutralize the scale disadvantage, a company has to constantly reconfigure its capabilities and understand its customers and their needs. Sevilla FC has, in the past decade, focused on centralizing its first-party data through a unified CRM platform. The platform allows the club to efficiently follow its members and followers to fill their needs by offering localized content, promotions, and materials, thus dismantling data silos and simplifying communication. The second significant change has been to modify the internationalisation entry method to favour data-driven decision-making and to prepare an audience fit before physically entering the market. The third change has been on the strategy concerning customer value, the shift from volume metrics to tracking lifetime value, and ensuring the depth of the database, instead of volume, exemplified by the comparison to the Barcelona- Spotify case. Concluding that the clubs' mechanisms of international strategy and market entry have shifted towards a multi-criteria checklist, where the traceable first-party database allows deeper analysis and ensures successful sponsorship negotiations and offerings, without higher risks or early physical investment. Ultimately, this thesis demonstrates that scale disadvantage can be overcome by strategic usage of assets, while contributing to the strategic management literature by implementing classical management theories and then applying them to an industry where the literature is limited. The thesis offers a generalizable analytical template demonstrating that agility, localised narrative differentiation, and data-driven customer-centricity can bypass scale barriers in highly competitive international markets.
Keywords: digitalisation; internationalisation; small and medium-sized enterprises; dynamic capabilities; resource-based view; first-party data; fan engagement; scale neutralisation; professional football; digital entry modes.